Finanças pessoais, endividamento familiar e qualidade de vida do servidor - Acordi, Francine Patricia Costa (2019)
Personal finances in general can cause concern and interfere in the individual’s quality of life. In this sense, a case of study was carried out at the Campus Medianeira of the Universidade Tecnológica Federal do Paraná (UTFPR). The research investigated the relationship between family indebtedness (in the context of personal finance and in the most varied forms of indebtedness) and the perception of the individual’s quality of life (public employee) according to the definition of quality of life from the World Health Organization (WHO). The hypotheses of this research were tested based on the data collected from the SIAPE System and the survey responses that were applied to the active and effective servers loaded in the analysis unit. The questionnaire on personal finances deepened the aspects of family indebtedness and behaviors on personal finances and the questionnaire on quality of life is the WHOQOL-BREF that was developed by WHO. For the analysis of the data was applied the statistical model of multiple linear regression. Statistical evidence of the alternative hypothesis 1 was found, that there is a relationship between personal finances and the individual's perception of quality of life, and the alternative hypothesis 2 was found, that there is a relationship between family indebtedness and the individual’s perception of quality of life, who refute the null hypotheses. Related to the analysis of hypotheses 3 and 4, that among the indebted families, "controlled" debt is associated with the better individual’s quality of life; and "excessive" indebtedness is associated with the poorer individual’s quality of life, no statistical evidence was found to refute the null hypotheses. The analyzes also suggest that the individual's perception of income availability is more important than the gross income actually received, that is, much more important than the income received is the perception that the money is sufficient to satisfy the needs.